Persepsi Pemustaka Terhadap Kualitas Layanan Perpustakaan Pascasarjana STAIN Pamekasan - Hairul A Cahyo (Pustakaloka, 2014)
Library is one of supporting element from institute, which can fullfill user’s information need for teaching learning process especially in postgraduate STAIN Pamekasan. To create optimal and good service in postgraduate library, it can see from user’s perception in service quality in postgraduate STAIN Pamekasan. This research used data collection technic; observation, interview and documentation. Officer quality in giving servive to user visible in copability and attitude from officer it self. Library service also can see from collection of books in library to fullfill user’s need. Supporting tools in building and rooms. To complete some tools, it also need infrastructure to fullfill library needs in service. Infrastructure needed are utensils, it means to support library actinity which unused up such as; bookshelf, table and chair, computer and internet, air conditioner, room’s light or lamp, catalogue and photocopy machine.